La influencia del método Kaizen en el proceso de mediación pedagógica para fortalecer la formación de hábitos lectores en estudiantes de tercer año de educación general básica en la escuela de educación básica Ángel Polibio Chaves, ubicada en el cantón Guaranda, provincia de Bolívar, período lectivo 2024-2025 - Armijos Romero, Anahi Thalia (2025)
The topic of the study was the Kaizen method in pedagogical mediation to foster reading habits in third-year General Basic Education children at the Ángel Polibio Chaves Basic Education School during the period of May-June 2025, the general objective was to identify effective strategies to improve teaching, a methodology was used that included methods, standards, curricular planning, and strategies with a socio-critical approach, the results revealed a positive impact of the Kaizen method in various pedagogical contexts, promoting active participation among students, through a dissertation and the analysis and interpretation of data obtained from an interview with 19 children from parallel A, these results were confirmed, suggesting the need to implement changes and strategies to improve classroom learning, highlighting the Kaizen method as an effective tool to enhance the quality of education and support the development of third-year (EGB) students in the educational unit.